The Dynamics of Tamil-Indian Community in Pre-Independence Indonesia: The Case of Deli Hindu Sabba in Medan - Maler, Wani; Mudzakkir, Moh.; Ikomatussuniah (Religi: Jurnal Studi Agama-agama, 2023)
This study traces the formation, development and decline of the Deli Hindu Sabba organization in the city of Medan, North Sumatra, Indonesia. This article examines the emergence of Indian Tamil community organizations in the pre-independence period of Indonesia. This paper uses historical research methods to reconstruct events in the past. Data obtained through literature study from various documents. The data obtained were processed using critical methods to determine the authenticity and validity of the data obtained. The analytical method used is descriptive narrative to describe the chronology of events and aspects that affect the course of events. The study found that the Deli Hindu Sabba organization had its ups and downs: it was founded in 1913 and had developed since, but it stopped conducting activities in 1918 until Kumarasamy took over this organization in 1928. After that, Kumarasamy was pivotal role in the development and activities of this organisation. These activities included providing free education with Tamil language guidance, Indian Boy Scout and Mother Paguthi to empower Tamil community in Medan. Besides that, various arts and sports activities were also carried out. However, the organization suffered a setback in 1942 when former chairman of organization converted into Buddhism, making the organization lacked the important figures that could become its spearhead. In addition, it is the same year of the Japanese occupation which had banned all organizations in Indonesia during that time. Keywords:Tamil-Indian Community; Deli Hindu Sabba; Formation; Development; Decline